Adaptability evaluation of distributed photovoltaic access to distribution network - XU Jiayu; LI Wei; SONG Baotong; WANG Fangmin; WANG Xiongfei; YANG Shuxia (Diance yu yibiao, 2025)
Adaptability evolution of distribution network is an important method to find weak links and put forward improvement suggestions from perspective of management decision-making. Based on the research results of the traditional distribution network adaptability, this paper analyzes the impact of distributed photovoltaic grid connection on the distribution network under the new situation, and constructs a comprehensive, reasonable and effective distribution network adaptability evolution index system from three dimensions of safety, economy and low carbon. With reference to the relevant standards, regulations and expert experience of distribution network construction, the calculation formula and scoring curve of each index is given. The combination of the OWA-AHP method and entropy weight method is used as index weighting to obtain the adaptability evaluation results of distribution network. Taking the actual distribution network in a certain region in China as an example, the adaptability difference of the distribution network before and after the access of distributed photovoltaic is analyzed. The results show that the access of distributed photovoltaic can effectively improve the adaptability of the distribution network. The evaluation method proposed in this paper can accurately locate the weak links of the adaptability on the basis of reflecting the adaptability of the distribution network, and provide a reference for the adaptability improvement plan of the distribution network.